A deletion variant Arg616 of androgen receptor in a Chinese family with complete androgen insensitivity syndrome - Ding, Leilei; Zhang, Duoduo; Yao, Fengxia; Luo, Min; Deng, Shan; Tian, Qinjie (Frontiers in Genetics, 2023)
Background Complete androgen insensitivity syndrome (CAIS) is one of disorders of sex development with X-linked recessive inheritance. Cases of CAIS usually presented as female phenotype, primary amenorrhea and/or inguinal hernia. Family aggregation is a rare scenario. Methods This study is a retrospective analysis of CAIS cases in a three-generation pedigree. Genotypes of patients were determined by sequencing the androgen receptor (AR) gene. The clinical data of the patients, including manifestations, hormone levels, and variants of the AR gene were analyzed. Results Sixteen people in this family were involved, a deletion mutation (c.1847_1849del; p. Arg616del) in exon3 of the AR gene that encodes the DNA binding domain was identified. Until now, four patients and four carriers were found in three generations of this family. The patients all live as female and one of them has been found with gonadal malignancy. Conclusions The present study identified a deletion mutation in a CAIS family of three generations involving four carriers and four patients, verified the genetic pattern and the corresponding clinical characteristics of CAIS. Moreover, a case with gonadal malignancy was discovered. The information of diagnosis and treatment in this pedigree is useful for the prenatal diagnosis and genetic counseling of similar family.